ANALISIS STRATEGI MANAJEMEN OPERASIONAL PADA UMKM KULINER: STUDI KASUS AYAM PENYET RAFFA DI MEDAN - Cut Nasiva Danil; Alya Ridha Nasution; Chelsy Nainggolan; Clara Pratama; Dionisius Sihombing; Marito Ritonga (Politeknik Negeri Lhokseumawe, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector play a vital role in the Indonesian economy, yet they face challenges of competition and limited resources. This study aims to analyze operational management strategies at Ayam Penyet Raffa MSME in Medan and identify the operational problems encountered. Using a qualitative approach with a case study method, data were collected through in-depth interviews with the business owner, direct observation, and documentation. The findings revealed five main problems: a